NONLINEAR DYNAMICS OF A ROTOR WITH CANTILEVERED DISK RESTING ON ANGULAR CONTACT BALL BEARINGS - Filipkovskyi, S.; Филипковский, С. В.; Філіпковський, С. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The mathematical model of nonlinear oscillations of the rotor resting on angular contact ball bearings is developed. The disc is fixed on the console end of the shaft. The deflection of the shaft, and the elastic deformation of the bearings have the same order. Analysis of free oscillations is carried out, using nonlinear normal modes. The modes and backbone curves of rotor nonlinear oscillations are calculated. The system has soft characteristics.
НЕЛИНЕЙНАЯ ДИНАМИКА РОТОРА С КОНСОЛЬНО ЗАКРЕПЛЁННЫМ ДИСКОМ НА РАДИАЛЬНО-УПОРНЫХ ШАРИКОПОДШИПНИКАХ
НЕЛІНІЙНА ДИНАМІКА РОТОРА З КОНСОЛЬНО ЗАКРІПЛЕНИМ ДИСКОМ НА РАДІАЛЬНО-УПОРНИХ ШАРИКОПІДШИПНИКАХ
Keywords: rotor; ball bearing; oscillations; nonlinear normal modes; backbone curves; ротор; шарикоподшипник; колебания; нелинейные нормальные формы; скелетные кривые; шарикопідшипник; коливання; нелінійні нормальні форми; скелетні криві; 534.1